Hubungan Tingkat Pengetahuan Swamedikasi Penyakit Ringan dengan Pengelolaan Limbah Obat di salah satu Pesantren di Karawang: The Relationship Between Knowledge of Self-Medication for Minor Illnesses and Drug Waste Management at an Islamic Boarding School in Karawang - Iqbal Ramdhani Asa’af; Indah Laily Hilmi; Munir Alinu Mulki (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2025)
Self-medication or self-treatment is an attempt by a person to treat themselves by recognizing the symptoms or illnesses they are experiencing and choosing their own medicine. However, in reality, self-medication is not accompanied by good drug waste management. So this study aims to measure students' knowledge about self-medication and drug waste management at Insan Harapan Islamic Boarding School and analyze the relationship between students' self-medication knowledge and drug waste management. The approach used in this study is the Cross-Sectional method. The study population consisted of all high school students at Insan Harapan Islamic Boarding School in Karawang, with a sample of 187 students selected using non-probability sampling. Data were analyzed using the spearman rank test. The results showed that 60% of respondents had a high level of knowledge about self-medication for minor illnesses, while 71% demonstrated good practices in drug waste management. This study also found a significant relationship between students' knowledge of self-medication for minor illnesses and their practices in drug waste management. The correlation test shows a significance p-value test is 0.01, which is less than 0.05, so it can be concluded that there is a relationship between the level of knowledge of self-medication for minor illnesses and the management of drug waste at the Insan Harapan Karawang Islamic Boarding School. However, this relationship is low with a coefficient correlation value of 0.25. These findings highlight the importance of enhancing health education on self-medication and drug waste management, as well as developing policies to regulate drug waste management to prevent adverse environmental impacts. Keywords: Self-medication; Knowledge; Waste; Medicine.